Characterization Of Variants Of Polyhydroxyalkanoate Synthase Of Cupriavidus Necator Generated By Error-Prone Polymerase Chain Reaction - Loh, Keat Lay (2013)
In this study, error-prone PCR of type I polyhydroxyalkanoate synthase (PhaCCn) from Cupriavidus necator was carried out to introduce random mutations in PhaCCn to investigate the functional importance of the substituted amino acids of PhaCCn, which to date, is structurally unknown.. Via this approach, mutant H8, which harboured five amino acid substitutions (I71T, I172T, P339L, N514S and S522R) was obtained. The H8 mutant exhibited low P(3HB) accumulation (0.1% CDW (Cell dry weight)) when compared to the wild-type (11.3% CDW). In terms of their positions in PhaCCn sequence, mutation I71T is located at the highly variable N-terminal domain of the PhaCCn, the mutation I172T is located in between the N-terminal and the conserved region, while mutations N514S, P339L and S522R were located in the α/β hydrolase fold region, which is highly conserved in all classes of PHA synthases.